Upaya Peningkatkan Hasil Belajar PKN Materi Kemerdekaan Mengemukakan Pendapat Dengan Metode CIRC Pada Siswa SMKN 58 - Anik Kurniatun (Universitas Cokroaminoto Yogyakarta, 2022)
This research is motivated by the implementation of traditional/conventional teaching and learning activities. This system only emphasizes conventional teaching approaches and Knowledge Transfer so that many students feel bored and are not interested in Civics lessons. This classroom action research was carried out in 3 cycles for 3 months. In this study the researchers collaborated with Civics subject teachers, all students of class X for the 2019-2020 academic year as well as data sources. The results of the study show that applying the Cooperative Integrated Reading and composition approach can improve student achievement in Civics subjects and increase student learning activities and can generate student interaction in the learning process. Student learning outcomes experienced an increase in mastery learning cycles 1, 2, and 3, namely 77.5%, 82.5% and 100%. This approach can overcome students who are slow learners so that they can interact and work together with other students. Thus the learning objectives designed by the teacher can be achieved. In this study the researchers suggested that every teacher's activities and steps in the learning process can apply learning models that can arouse students' enthusiasm, especially the Cooperative Integrated Reading and Composition (CIRC) approach.